Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.clim.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

IgA nephropathy enigma

Abstract: IgA nephropathy (IgAN) is the leading cause of primary glomerulonephritis in the world. The disease is characterized by the presence of immune complexes in the circulation and in mesangial deposits with ensuing glomerular injury. Although in humans there are two IgA subclasses, only IgA1 molecules are involved. The exclusivity of participation of IgA1 in IgAN prompted extensive structural and immunological studies of the unique hinge region (HR) of IgA1, which is absent in otherwise highly homologous IgA2. HR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 68 publications
0
36
0
Order By: Relevance
“…57 In primary IgAN, the tissue origin of galactose-deficient IgA1 (Gd-IgA1) is still debated, but evidence indicates its mucosal origin: (i) Gd-IgA1 in mesangial deposits is polymeric, typical of IgA1 produced in mucosal tissues; (ii) macroscopic hematuria frequently manifests during an active respiratory tract and gastrointestinal tract infection; and (iii) polymeric IgA1 produced at mucosal sites has a higher capacity for binding to a lectin specific for N-acetylgalactosamine (the terminal sugar in galactose-deficient glycans of Gd-IgA1) than does serum IgA1 in healthy individuals. 58,59 In contrast, other studies support the concept that polymeric IgA1 is produced in the bone marrow in patients with IgAN. 58 Thus, it has been postulated that patients with IgAN have IgA1-producing cells with altered homing receptors when migrating from an inductive site to an effector site in gut mucosa and therefore mistakenly "home" to the bone marrow.…”
Section: Liver Diseasementioning
confidence: 97%
See 1 more Smart Citation
“…57 In primary IgAN, the tissue origin of galactose-deficient IgA1 (Gd-IgA1) is still debated, but evidence indicates its mucosal origin: (i) Gd-IgA1 in mesangial deposits is polymeric, typical of IgA1 produced in mucosal tissues; (ii) macroscopic hematuria frequently manifests during an active respiratory tract and gastrointestinal tract infection; and (iii) polymeric IgA1 produced at mucosal sites has a higher capacity for binding to a lectin specific for N-acetylgalactosamine (the terminal sugar in galactose-deficient glycans of Gd-IgA1) than does serum IgA1 in healthy individuals. 58,59 In contrast, other studies support the concept that polymeric IgA1 is produced in the bone marrow in patients with IgAN. 58 Thus, it has been postulated that patients with IgAN have IgA1-producing cells with altered homing receptors when migrating from an inductive site to an effector site in gut mucosa and therefore mistakenly "home" to the bone marrow.…”
Section: Liver Diseasementioning
confidence: 97%
“…58,59 In contrast, other studies support the concept that polymeric IgA1 is produced in the bone marrow in patients with IgAN. 58 Thus, it has been postulated that patients with IgAN have IgA1-producing cells with altered homing receptors when migrating from an inductive site to an effector site in gut mucosa and therefore mistakenly "home" to the bone marrow. 5 TCD mechanisms involve 2 pathways: (i) CD40L on activated effector T cells and its interaction with CD40 on B cells; and (ii) involvement of cytokines, transforming growth factor, and interleukins.…”
Section: Liver Diseasementioning
confidence: 97%
“…A significant number of IgAV patients require ongoing symptomatic and/or immune modulating treatment and disease relapses have been described in up to 30% of patients [14,15]. Earlier work has shown that the typical abnormalities in IgA glycosylation in IgAV may have a hereditary base [16] leading to possibly continued production of abnormally glycosylated IgA1 and increased risk for conditions associated with abnormal IgA levels and/or function [17][18][19][20]. The two pathways combined constitute risk factors for subsequent development of comorbidity in IgAV patients.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrantly glycosylated IgA1 might be recognized as an autoantigen, and thus the immune response against it may lead to the production of anti-IgA1-antibodies. However, of interest, more recent studies suggest that some pathogens such as Epstein-Barr virus and Streptococcus bacteria possess GalNAc-containing structures on their surfaces, which might subsequently cross-react with glycans on IgA1 resulting in the formation of pathological immune complexes 29 - 31 . This 'molecular mimicry' might explain the association of macroscopic hematuria with upper respiratory tract infections 23 .…”
Section: Antigen Presentation By Immunoproteasomementioning
confidence: 99%